Public Spending on Education in Latin America Does It Pay? - Zoido, Pablo (OECD Development Centre Policy Insights, 2008)
Education is one of the most important drivers of economic growth. The benefits of education go beyond the academic, contributing to economic objectives such as growth and productivity, as well as to social goals such as health and social cohesion. In a highly competitive, globalised world economy, public spending on education is more important than ever